Familial spinocerebellar degeneration as an expression of adrenoleukodystrophy. Issue 12 (December 1986) - Kobayashi, T; Noda, S; Umezaki, H; Goto, I; Suzuki, S; Kitaguchi, T; Kuroiwa, Y
Abstract : A family with adrenoleukodystrophy and clinical manifestations of spinocerebellar degeneration was studied. Two adult male first cousins showed progressive limb and truncal ataxia, slurred speech and spasticity of the extremities. Brain CT scans demonstrated atrophy of the pons and cerebellum, in both cases. Very long chain fatty acids in plasma and erythrocyte membranes were elevated in the affected patients and intermediately increased in an aunt and the mother of one patient, thereby indicating homozygotes and carriers of adrenoleukodystrophy, respectively. This unusual type of adrenoleukodystrophy seems to be transmitted as an X-linked recessive trait.